The efficacy of 16S ribosomal DNA sequencing in the diagnosis of bacteria from blood, bone and synovial fluid samples of children with musculoskeletal infections. (1st April 2018) - Hashavya, S.; Gross, I.; Michael-Gayego, A.; Simanovsky, N.; Lamdan, R.
Abstract: Background: Musculoskeletal infections are among the most common bacterial infections in children leading to hospitalization, invasive procedures and prolonged antibiotic administration. Blood, synovial and sometimes tissue cultures are essential for the diagnosis and treatment of musculoskeletal infections; 16S ribosomal DNA (rDNA) sequencing is a novel diagnostic tool for the detection of bacteria. While the yield of 16S rDNA sequencing in synovial fluid was previously assessed, data regarding the efficacy of this method from blood samples or partially treated children with suspected musculoskeletal infections is lacking. In this study we assessed the yield of 16S rDNA sequencing in blood, bone and synovial samples of children with musculoskeletal infections. Methods: Blood, synovial and bone samples were collected from children with suspected musculoskeletal infections and analyzed for the presence of 16S rDNA, the results were then compared with the benchmark microbial cultures. Results: During the study period, 41 children (18 boys and 23 girls) with suspected acute musculoskeletal infection were enrolled. A positive blood culture was found in 6/31 cases (19.4%) with methicillin-susceptible Staphylococcus aureus being the most commonly isolated bacterium. No significant 16S rDNA detection in blood samples was recorded. Synovial fluid culture was positive in 6/28 samples (21%), Kingella kingae being the most common pathogen. When using the 16S rDNA sequencing method, the rate of positive results in synovial fluid was higher with bacterial detection in 12/23 (52%) samples. The 16S rDNA sequencing method was also able to identify pathogens in samples taken from partially treated children where cultures were negative with 16S rDNA detection in 5/5 samples. Conclusion: Although 16S rDNA sequencing may increase the yield of bacterial detection in synovial samples of patients with musculoskeletal infections, there is no benefit from applying this method on blood samples. The 16S rDNA sequencing method may be particularly beneficial when antibiotic treatment was started prior to synovial fluid sampling. Level of Evidence: Level-II diagnostic study